Is there an optimal initial amount of activation for midpalatal suture expansion? - Alyessary, Akram S.; Yap, Adrian U-Jin; Othman, Siti Adibah; Rahman, Mohammad Tariqur; AL-Namnam, Nisreen Mohammed; Radzi, Zamri (Springer Verlag, 2018)
Objective: Accelerated bone-borne expansion protocols on sutural separation and sutural bone formation were evaluated via histomorphometry and immunohistochemistry to determine the optimal initial activation without disruption of bone formation. Materials and methods: Sixteen New Zealand white rabbits were randomly divided into four groups. Modified Hyrax expanders were placed across the midsagittal sutures and secured with miniscrew implants with the following activations: group 1 (control), 0.5 mm expansion/day for 12 days; group 2, 1 mm instant expansion followed by 0.5 mm expansion/day for 10 days; group 3, 2.5 mm instant expansion followed by 0.5 mm expansion/day for 7 days; and group 4, 4 mm instant expansion followed by 0.5 mm expansion/day for 4 days. After 6 weeks, sutural expansion and new bone formation were evaluated histomorphometrically. Statistical analysis was performed using Kruskal–Wallis/Mann–Whitney U tests and Spearman’s rho correlation (p < 0.05). Results: The smallest median sutural separation was observed in group 1 (3.05 mm) and the greatest in group 4 (4.57 mm). The lowest and highest amount of bone formation were observed in group 4 (55.82%) and in group 3 (66.93%), respectively. Immunohistochemical analysis revealed significant differences in median levels of alkaline phosphatase and osteopontin expression between all experimental groups. The highest level of these proteins was attained in group 3, followed by groups 2, 1, and 4, respectively. Conclusions: Sutural appositional bone formation corresponded with the amount of initial expansion to a point. When initial expansion was increased to 4 mm, sutural bone remodeling was disturbed and new bone formation was decreased. The most effective sutural expansion was achieved with 2.5 mm initial activation followed by 0.5 mm expansion/day for 7 days.